New porphyrin amino acid conjugates: synthesis and photodynamic effect in human epithelial cells - Serra, V. Vaz (2022)
The efficacy of new porphyrin amino acid conjugates as photosensitizers for photodynamic therapy (PDT) were assayed in vitro on tumoral (HeLa) and on non tumoral (HaCaT) human cell lines. The conjugates stable in liposomes are able to penetrate efficiently in the cytoplasm of cultured cancer and normal cells. No dark cytotoxicity is observed at the same concentration used for PDT cell treatment and during long incubation time (24h). The cell survival after the PDT treatment with visible light is dependent upon light exposure level and compound concentration. The tested compounds show higher photocytotoxicity in tumoral HeLa cells than in no tumoral HaCaT cells. The results suggest that these amino acid porphyrin conjugates are potential photosensitizers for PDT.